Work Posture Evaluation on Ergonomic “Colet” Workbench Design in Batik Coloring Process using Rapid Entire Body Assessment and Nordic Body Map - Amalia Amalia; Rudy Tjahyono; Jazuli Jazuli; Rodia Syamwil (OPSI, 2021)
The effort to preserve batik is to maintain the continuity of batik production. Coloring process is one of the important processes in batik production. In addition to the dyeing technique, there is a “colet” technique in batik coloring process. Colet technique is considered an efficient technique in saving coloring dyes. The colet process is still carried out without standards and does not consider ergonomic aspects. This study aims to analyze the risk level of batik workers posture in colet technique coloring process. This research is an observational study with data analysis using the Rapid Entire Body Assessment (REBA) and Nordic Body Map (NBM). Based on the measurement, the risk level with the initial work posture has a score 9 and 7, which means the posture needs immediate corrective action to prevent occupational diseases. The implementation of Ergonomic “Colet” workbench is a way to improve work posture so the risk could be decreased, with score 4 both in standing and sitting working position.